Static and dynamic corrosion behavior of SnO2‐doped AZS slip cast refractory in SLS glass - Toperesu, Phillip Masimba; Kale, Girish M.; Daji, Jafar; Parkinson, David E.; Parkinson, Simon (International journal of applied ceramic technology, 2022)
The corrosion behavior of a tin IV oxide‐doped AZS‐refractory, subject to static and dynamic corrosion testing at 1370˚C in soda‐lime‐silica glass, was studied considering the effect of the microstructural features on corrosion. The refractory was synthesized by slip cast methods through reaction sintering of alumina and zircon raw materials using SnO2 as a sintering agent. SnO2 had a considerable influence in the enhanced alumina/zircon reaction sintering and the subsequently evolved microstructures of an interlocked Zr(1‐x)Sn(x)O2 solid solution reinforced alumina‐mullite composite. The process kinetics of the refractory corrosion followed reasonably well the predicted dependence on the square root of angular velocity under forced convection corrosion. Glass chemical corrosion and erosion of the refractory, under static and dynamic glass conditions, respectively, revealed the Zr(1‐x)Sn(x)O2 solid solution‐rich mullite matrix as providing the most corrosion resistance and glass compatibility.